Implementasi Kebijakan Co-Branding Jogjamark, 100% Jogja dan Jogja Tradition Provinsi Daerah Istimewa Yogyakarta Dalam Pengembangan UMKM Maharani Ajeng Putri Linanjung - Maharani Ajeng Putri Linanjung; Wahid - Abdulrahman (Journal of Politic and Government Studies, 2020)
The efforts of the Government of Yogyakarta Special Regional Province in dealing with the Asean Economic Community (MEA) by creating Governor Regulation No.21 of 2017 concerning Licensing Of Jogjamark Co-Branding, 100% Jogja and Jogja Tradition in Mining MSMEs. This is done to build a good reputation and provide identity to the area's original products. The research method used qualitative descriptive using van meter van horn policy implementation theory. The data obtained is then analyzed using Triangulation, Theory and Data Sources. The findings of this study show the implementation of the policy is carried out in accordance with what has been prepared in Pergub No. 21 of 2017. There are several obstacles that occur such as lack of socialization, lack of human resources and lack of coordination between BPKI UPT and OPD in each district or city resulting in a lack of msmMEs registered in Co-Branding. Given the large number of MSMEs located in the DIY region. Based on the conclusion, the advice that can be given is that the implementation will be more maximal if the implementing agent of UPT BPKI equalizes socialization and coordination to other OPD to cooperate in implementing the policies of Co-Branding Jogjamark, 100% Jogja and Jogja Traditon